Individualism vs. collectivism: How inherited cultural values affect labor market outcomes of second generation immigrants in the US - Lisa Sofie Höckel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The labor market performance of second generation immigrants is a crucial determinant of integration. Labor market returns to their different cultural traits, however, have been rarely researched within the economic literature. This study provides insight on the link between the level of collectivism at the country of ancestry and labor market outcome of second generation immigrants in the US. Using 1994 - 2014 survey data, we analyze the relationship between inherited cultural values and the economic outcome of more than 21,000 male homogamous second generation immigrants. We use the historical disease environment of the country of ancestry as a measurement for collectivism since collectivistic values have been particularly advantageous in countries with a greater prevalence of disease-causing pathogens. We find that higher scores of collectivism are associated with higher labor force participation and income earned in the US. The number of hours worked and self-selection into jobs that require collectivistic traits are the main determinants of the positive impact of collectivism on earnings. – – Die Integration von Migranten im Aufnahmeland ist stark mit deren Erfolg am Arbeitsmarkt verbunden. Für letzteres können kulturelle Werte eine entscheidende Einflussgröße darstellen. Die ökonomische Literatur hat den Einfluss von kulturellen Werten auf die Arbeitsmarktpartizipation von Migranten bisher jedoch kaum untersucht. Daher analysiert dieses Papier den Zusammenhang zwischen kollektivistischen Werten im Herkunftsland und der Arbeitsmarktsituation von Migranten der zweiten Generation (Einwandererkinder). Die empirische Analyse wird mit Hilfe von US amerikanischen Umfragedaten von mehr als 21 000 männlichen Immigranten der zweiten Generation durchgeführt. Kollektivistische Werte werden anhand historischer Daten zur Verbreitung bestimmter Krankheitserreger in den Herkunftsländern gemessen, da kollektivistische Werte in Gebieten mit einer hohen Erregerdichte vorteilhaft sind. Unsere Ergebnisse zeigen, dass ein höherer Grad an Kollektivismus im Herkunftsland mit höherer Arbeitsmarktbeteiligung und höherem Einkommen in den USA verbunden ist. Dieser positive Zusammenhang wird im Wesentlichen durch die Anzahl der gearbeiteten Stunden sowie der Wahl des Berufes erklärt.
Keywords: A13; F22; J14; J24; 330; labor force participation; occupational choice; migration; cultural values